Bureaucratic Reform and Clean Governance: Efforts Towards Social Justice and Sustainable Economic Growth in Indonesia - Ibrahim, Riza Andrian; Sidiq, Fahmi; Azahra, Astrid Sulistya (Communication in Research and Publications (CRP), 2023)
The implementation of a clean government free from corrupt behavior is a crucial aspect in ensuring sustainable economic growth and development in Indonesia. This article discusses the urgency of bureaucratic reform as a first step in overcoming various obstacles affecting the effectiveness of government. Institutional structuring, management, and human resources, as well as strengthening accountability are the main focuses of reform efforts. In addition, active community participation, firm law enforcement, transparency, and responsiveness to public needs are also important elements in good governance. Through the implementation of these principles, it is hoped that Indonesia can build a government system that is transparent, accountable, and able to provide quality services to all people.